1996
DOI: 10.3109/17453679608997769
|View full text |Cite
|
Sign up to set email alerts
|

Ankle stability without the lateral malleolus—a report of 2 cases

Abstract: A 30-year-old man fell out of his motorboat and the screw of his outboard engine hit his left ankle, resulting in a 10 x 20 cm open wound, with large skinflap on the lateral side of the ankle. The lateral malleolus had disappeared (Figure 1). The talus was uncovered but the peroneal tendons were intact. In spite of the pain, the plantar and dorsal flexions were normal and stability was remarkably good.After debridement, the wound was closed. The ankle was immobilized in a below-knee leg cast. For 5 days i.v. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…After resection of a fibular segment leaving a caudal segment < 8 cm, six patients suffered an instability; in three, this was associated with cranial migration of the lateral malleolus as well. In contrast, several authors [18][19][20] reported that even years after resection of the distal fibula due to tumor, the tibiota- lar joint showed a normal configuration and no instability.…”
Section: Discussionmentioning
confidence: 95%
“…After resection of a fibular segment leaving a caudal segment < 8 cm, six patients suffered an instability; in three, this was associated with cranial migration of the lateral malleolus as well. In contrast, several authors [18][19][20] reported that even years after resection of the distal fibula due to tumor, the tibiota- lar joint showed a normal configuration and no instability.…”
Section: Discussionmentioning
confidence: 95%